Effects of automated speed control on speeding intention and behavior on mixed-traffic urban arterial roads - Phongphan Tankasem; Thaned Satiennam; Wichuda Satiennam; Sittha Jaensirisak; Wiroj Rujopakarn (IATSS Research, 2022)
Although the effectiveness of automated speed control (ASC) has been proven, the mechanism of behavioral change in developing countries remains unclear. The objective of this study was to elucidate the effect of ASC on drivers' speeding intention and behavior on mixed-traffic urban arterial roads. Before and during the implementation of ASC, questionnaires based on the theory of planned behavior (TPB) were administered to local passenger-vehicle drivers. A total of 200 participants with an average age of 38.4 years completed both survey waves. To explain the mechanism of behavioral change, the multiple indicators multiple causes (MIMIC) structural equation modeling (SEM) time-invariant was used simultaneously for both waves. The model explained 49% and 55% of the variance in intention, and 40% and 56% of the variance in self-reported speeding behavior, respectively, before and during the ASC implementation period. The findings reveal that ASC altered the cognitive factors of speeding behavior. Speeding became less favorable, had lower approval, and was more difficult to control. Drivers reported lower speeding tendency and diminished speeding behavior. Furthermore, the ASC changed the relative impact of the factors, boosted the influence of family members and close friends on drivers' speeding motivation, and increased the influence of intention and perceived control on speeding behavior. This paper provides recommendations for the implementation of ASCs on mixed-traffic urban arterial roads in developing countries.